2021
DOI: 10.3390/jcs5100260
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Combustion Properties of Corncob Biomass via Torrefaction for Solid Fuel Applications

Abstract: The overdependence on fossils as the primary energy source has led to climate change, global warming, and the emission of greenhouse gas. As a result, the United Nations, while setting the goals for the year 2030, has made the provision of a green environment and energy one of the top priorities. In this study, the suitability of corncob for green energy production was investigated. The improvement of corncob’s thermal and combustion properties via the torrefaction process was considered for solid fuel applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Previously, Pitak et al [29] reported fuel ratios in the range of 0.3-0.6 for different biomasses. In another study, Ibitoye et al [30] reported a fuel ratio of 1.29 for torrefied corn cobs at 260 and 60 min. Sarker et.…”
Section: Fuel Ratiomentioning
confidence: 93%
“…Previously, Pitak et al [29] reported fuel ratios in the range of 0.3-0.6 for different biomasses. In another study, Ibitoye et al [30] reported a fuel ratio of 1.29 for torrefied corn cobs at 260 and 60 min. Sarker et.…”
Section: Fuel Ratiomentioning
confidence: 93%
“…Various cutting-edge technologies are used to manufacture biochar, including pyrolysis (Mishra and Mohanty 2021 ), gasification (Ibitoye et al 2021b ), hydrothermal carbonization (HTC) (Ibitoye et al, 2022 ; Ibitoye et al 2023b ), torrefaction (Ibitoye et al 2021c ), and even innovative methods like microwave pyrolysis (Gabhane et al 2020 ), and plasma pyrolysis (Bhatt et al 2022 ). The viability of these methods is influenced by several parameters, including the type of feedstock, catalysts utilized, temperature, heating rates, and the configuration of the reactor (Alahakoon et al 2022 ; Panwar et al 2019 ; Uday et al 2022 ; Zhang et al 2022 ).…”
Section: Biochar Production Techniquesmentioning
confidence: 99%
“…-Challenges in mass production. -Moderate biochar yield Moderate (Abdelhadi et al 2017 ; Chyuan et al 2021 ; Govindaraju et al 2022 ; Ibitoye et al 2021b , c , 2022a , c ; Safarian 2023a ; Thengane et al 2020 ; Yılgın et al 2019 ) …”
Section: Biochar Production Techniquesmentioning
confidence: 99%
“…Many authors reported that the attained optimal condition for biomass torrefaction yields an enhancement factor of around 1.3-1.4. Ibitoye et al (2021) stated that a corncob that was torrefied at 260 °C for 60 minutes with an enhancement factor of 1.34 demonstrated the best thermal and combustion properties [Ibitoye et al, 2021]. In turn, claimed that for the pretreatment of rice husk and Sapindus pericarp , the appropriate torrefaction conditions may be found at roughly 280 °C (30 min) and 360 °C (0 min), with the enhancement factor being 1.36 and 1.41, respectively.…”
Section: The Optimal Condition For Torrefactionmentioning
confidence: 99%